Nonlinear dynamics and chaos with applications to hydrodynamics and hydrological modelling - Velickov Slavco (London Taylor & Francis, 2004)
The theory of nonlinear dynamics and chaos and the extent to which recent improvements in the understanding of inherently nonlinear natural processes present challenges to the use of the mathematical models in the analysis of water and environmental syste
Dissertation submitted for the Doctorate of Delft University of Technology, Netherlands
Keywords: Chaos; Chaotic behavior in systems; Dynamic systems; Nonlinear dynamics